Periodicities in the dates of onset of the southwest monsoon over Kerala - KANE, R. P. (MAUSAM, 1980)
A Burg (MEM) spectrum analysis of the dates of onset of the SW monsoon over Kerala as given (a) IMD, (b) Ananthakrishnan et al. (1967) and (c) Ramdas et al. (1954) revealed periodicities of about Tk= 2.3, 2.8, 3.5, 3.9, 4.7, 5.5, 6.2, 7.3, 8.5, 10.8, 14, 20 and 40 years with amplitudes of about 2-5 days. When used for prediction, the match was within ±5 days for the series of Ananthakrishnan et al. (1967) and within ± 10 days for the IMD series and the series of Ramdas et al. (1954).